Expression of Matrix Metalloproteinase-9 at the Endometrium in Intramural Uterine Myoma with Heavy Menstrual Bleeding and Non Heavy Menstrual Bleeding.: Ekspresi Mmp-9 di Endometrium Mioma Uteri Intra Mural yang Mengalami Heavy Mestrual Bleeding dan Non Heavy Mestrual Bleeding - Effendi, K Yusuf (Sriwijaya Journal of Medicine, 2018)
Bleeding that occurs in intramural myoma to date have not revealed the clear mechanism. Presumably, the decrease of progesteron and estrogen by the time of menstruation occurs (progesterone withdrawal) wil decrease the TIMP which inhibit the production and release of MMP. TIMP reduction will lead escalation of MMP expression. This study aims to analyze the expression of MMP-9 in intramural myoma. Crosssectional study involve two group of study, case and control (intramural uterine myoma women without heavy mestrual bleeding[HMB]), Endometrial biopsy were performed on both group, and the expression of MMP-9 were checked using immunohistochemistry. This study shows t-test analysis was performed on case group and MMP-9 was found to be significantly affecting the bleeding outcome (p = 0,003) with pravalence ratio of 1,047 (1,016 – 1,079) which indicate that MMP-9 increase 1,047 the risk of bleeding.